2003
DOI: 10.1038/ng1220
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Stk6/STK15 as a candidate low-penetrance tumor-susceptibility gene in mouse and human

Abstract: Linkage analysis and haplotype mapping in interspecific mouse crosses (Mus musculus x Mus spretus) identified the gene encoding Aurora2 (Stk6 in mouse and STK15 in human) as a candidate skin tumor susceptibility gene. The Stk6 allele inherited from the susceptible M. musculus parent was overexpressed in normal cells and preferentially amplified in tumor cells from F(1) hybrid mice. We identified a common genetic variant in STK15 (resulting in the amino acid substitution F31I) that is preferentially amplified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
276
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(291 citation statements)
references
References 35 publications
14
276
1
Order By: Relevance
“…15 AURKA binds and phosphorylates BRCA1, and it was suggested that this BRCA1 phosphorylation plays a role in G2/M transition. 16 The AURKA gene has been recently identified as a low-penetrance tumor susceptibility gene, 17 and was subsequently analyzed for its implication with breast cancer albeit leading conflicting results. [18][19][20][21][22][23][24][25][26][27] BAP1 is an ubiquitin carboxy-terminal hydrolase which binds to the BRCA1 RING finger domain and enhances BRCA1 growth suppression properties.…”
Section: Introductionmentioning
confidence: 99%
“…15 AURKA binds and phosphorylates BRCA1, and it was suggested that this BRCA1 phosphorylation plays a role in G2/M transition. 16 The AURKA gene has been recently identified as a low-penetrance tumor susceptibility gene, 17 and was subsequently analyzed for its implication with breast cancer albeit leading conflicting results. [18][19][20][21][22][23][24][25][26][27] BAP1 is an ubiquitin carboxy-terminal hydrolase which binds to the BRCA1 RING finger domain and enhances BRCA1 growth suppression properties.…”
Section: Introductionmentioning
confidence: 99%
“…The STK15 gene (also known as AURKA, STK6, and BTAK) encodes Aurora-A, a serine-threonine kinase that acts as a key regulator of mitotic chromosome segregation and is particularly involved in the passage from the G 2 to the M phase of the cell cycle (5,6). Defects in chromatid segregation cause genetic instability, a condition that is clearly associated with tumorigenesis (7).…”
Section: Introductionmentioning
confidence: 99%
“…As the frequency of genotypes in controls in the other studies are not significantly different from those expected, there is little evidence that overt population stratification underpins study heterogeneity. Although there is some data to suggest that F31I has functional cellular consequences (Ewart-Toland et al, 2003;Kimura et al, 2005), direct causality has not been demonstrated. It is possible that population-specific linkage disequilibrium with another functional variant could be operating.…”
Section: Discussionmentioning
confidence: 99%
“…(Dutertre et al, 2002) and plays a role in the development of malignancy (Bischoff et al, 1998;Zhou et al, 1998;Ewart-Toland et al, 2003). Recently, the T91A singlenucleotide polymorphism (SNP) in STK15, which generates the substitution F31I, and has been reported to influence genomic instability (Ewart-Toland et al, 2003;Kimura et al, 2005), has been proposed as a low penetrance variant for a number of tumours including colorectal cancer (CRC) (Ewart-Toland et al, 2003. To further evaluate the relationship between STK15 F31I and risk of CRC, we genotyped 2558 CRC cases and 2680 controls for this polymorphism.…”
mentioning
confidence: 99%